An extensible driving model for multiple grayscales colorful electrowetting displays - Zhang, Taiyuan; Guo, Yuanyuan; Deng, Yong; Sun, Hailing (Frontiers in Physics, 2022)
As a new type of reflective display technology with paper-like display performance, electrowetting display (EWD) can realize ultra-low power consumption, wide viewing angle and fast response speed. In order to apply the EWD to the large-size display field, an extensible driving model for multiple grayscales colorful EWDs was proposed in this paper. The proposed driving model consisted of a grayscale model, a colorful display model and an extensible driving model. With the grayscale model and the colorful display model, the driving waveform of the colorful grayscale display was designed based on limited output voltage levels of a general-purpose graphic driver chip. And then, the extensible driving model was used to realize the large-size display large-scale display based on a matrix of small-size EWD panels. In addition, an experimental platform, which was composed of the display panel and the driving board with a data interface, was designed based on the proposed models. Experimental results showed that it could realize an 18-bit colorful dynamic display on the extended display matrix with a resolution of 48*16. It was indicated that the display matrix could be used for multiple grayscales and colorful dynamic displays by applying the proposed driving models. The research has brought about a way of enlarging the size of the EWD, which is conducive to broadening the scope of application of EWDs.